Evaluation of Islamic websites’ content reliability - Mohammad Nassr, Rasheed; Mahmud, Murni; Aliyu, Mansur (2015)
Internet is an open platform for anyone to publish and share information without being subjected to the authenticity of information. For Muslims, religious information crucially should be reliable due to the very reason that many Muslims consider the Internet as a source in getting Islamic knowledge. Unfortunately, the assessment on reliability of the information provided by the Internet is complex. The huge amounts of data available and lack of knowledge among Muslims contribute to the users’ incapability to recognize existences of unreliable information. Focusing on the reliability of information, this paper presents a software prototype, which uniquely automates and processes the reliability evaluation through inspections of references and scholars that are cited in the Islamic websites. Those references indicate that the Islamic websites derived their information from reliable religious sources.